Clinical benefit of early treatment with bone‐modifying agents for preventing skeletal‐related events in patients with genitourinary cancer with bone metastasis: A multi‐institutional retrospective study. (18th March 2019) - Owari, Takuya; Miyake, Makito; Nakai, Yasushi; Hori, Shunta; Tomizawa, Mitsuru; Ichikawa, Kazuki; Shimizu, Takuto; Iida, Kota; Samma, Shoji; Iemura, Yusuke; Momose, Hitoshi; Omori, Chihiro; et al.
Abstract : Objectives: To evaluate the clinical benefit of bone‐modifying agents and identify the risk factors of skeletal‐related events in patients with genitourinary cancer with newly diagnosed bone metastasis. Methods: This was a multicenter retrospective study including a total of 650 patients with bone metastasis of the following cancer types: hormone‐sensitive prostate cancer ( n  = 443), castration‐resistant prostate cancer ( n  = 50), renal cell carcinoma ( n  = 80) and urothelial carcinoma ( n  = 77). Clinical factors at the time of diagnosis of bone metastasis were analyzed. Early treatment with bone‐modifying agents was defined as follows: administration of bone‐modifying agents before the development of skeletal‐related events and within 6 months from the diagnosis of bone metastasis. Results: During the follow‐up period (median 19.0 months, interquartile range 6.0–43.8 months), skeletal‐related events were reported in 88 (20%) patients with hormone‐sensitive prostate cancer, 17 (34%) patients with castration‐resistant prostate cancer, 58 (73%) patients with renal cell carcinoma and 34 (44%) patients with urothelial carcinoma. Early treatment with bone‐modifying agents significantly prolonged the time to the first skeletal‐related event in castration‐resistant prostate cancer, renal cell carcinoma and urothelial carcinoma, but not in hormone‐sensitive prostate cancer. Bone pain and elevated alkaline phosphatase levels were independent predictive risk factors of the first skeletal‐related event. The subgroup analysis showed that early treatment with bone‐modifying agents was associated with prolonged time to the first skeletal‐related events in patients with bone pain or elevated alkaline phosphatase levels. Conclusions: Early treatment with bone‐modifying agents should be considered, especially for patients with bone pain and elevated alkaline phosphatase levels, to prevent skeletal‐related events in patients with genitourinary cancer with bone metastasis.